2010
DOI: 10.1017/s000748530999071x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the antibacterial activity in larval excretion/secretion of four species of insects recorded in association with corpses, using Lucilia sericata Meigen as the marker species

Abstract: The relative antibacterial activities of excretion/secretion (ES) from two carrionfeeding insects, Calliphora vicina Robineau-Desvoidy and Dermestes maculatus DeGeer, and a detritivore, Tenebrio molitor Linnaeus, were compared to that of Lucilia sericata Meigen, a species with ES of known antibacterial capacity, in order to explore the antimicrobial potential of other carrion and detritivore species. Viable counts were used to assess time-kill of ES against five bacterial species, Staphylococcus aureus, Escher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 20 publications
(36 reference statements)
2
29
0
6
Order By: Relevance
“…This is in concordance with findings of Huberman et al (2007) and Barnes et al (2010) on L. sericata hemolymph extract and ES, respectively, where significant bactericidal activity against P. aeruginosa than against S. aureus were recorded. Also, Teh et al (2013) found that L. cuprina larval methanol extracts at 0.78 and 1.56 mg/ml concentrations were able to inhibit more than 50% of P. aeruginosa and E. coli, respectively, while 3.13 mg/ml was necessary to inhibit 50% bacterial growth of Klebsiella pneumonia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in concordance with findings of Huberman et al (2007) and Barnes et al (2010) on L. sericata hemolymph extract and ES, respectively, where significant bactericidal activity against P. aeruginosa than against S. aureus were recorded. Also, Teh et al (2013) found that L. cuprina larval methanol extracts at 0.78 and 1.56 mg/ml concentrations were able to inhibit more than 50% of P. aeruginosa and E. coli, respectively, while 3.13 mg/ml was necessary to inhibit 50% bacterial growth of Klebsiella pneumonia.…”
Section: Discussionsupporting
confidence: 92%
“…The antimicrobial actions against a variety of Gram+ve and Gram-ve bacteria were studied from maggot's ES of L. sericata (Daeschlein et al, 2007;Huberman et al, 2007;Jaklic et al, 2008), Lucilia cuprina (Arora et al, 2010;El Shazely et al, 2013), Calliphora vicina (Barnes et al, 2010) and three Chrysomya species (Ratcliffe et al, 2015). Currently, there is a tendency to use modern biosurgery (that is, maggot therapy without maggots) instead of traditional biosurgery (Vilcinskas, 2011), where maggot's derivatives or active molecules could be therapeutically used in either their native or recombinant/synthetic form to face the antibiotic-resistant bacteria in hospitals and communities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are many biotic and abiotic factors that may affect the oviposition of blow ßies. For example, the microorganisms on the corpse might strongly inßuence the growth of maggots (Barnes et al 2010). The bacterial activity on the corpse might thus also be one of the important factors on the blow ßy oviposition.…”
Section: Influence Of Intra-and Interspecific Interactionsmentioning
confidence: 99%
“…Thus different blow fly species may have evolved different relationships with the range of microbial species found on the corpse. Examples of such relationships have been demonstrated in previous studies, including species variation in levels of antimicrobial activity against specific bacteria [39] and ovipositional response to different bacterial species [40][41]. This relationship would extend to the temporal dimension as well, with microbial communities being dynamic through time [15,42] and species of blow flies laying eggs on the corpse at different times.…”
Section: Discussionmentioning
confidence: 80%